Transformaciones urbanas en León, siglo XX - García Gómez, Miguel Ángel (Universidad Michoacana de San Nicolas de Hidalgo. Universidad Autónoma de Aguascalientes. Universidad de Colima. Universidad de Guanajuato, 2007)
The urban transformations in León of the XXth century are the topic of this investigation, the city that is studied, that in the beginning of century would have an urban premodern form, towards the end of the same century would have transformed in an urban form with metropolitan characteristics, happening of being the materialized space of a society of hundred thousand inhabitants, to an agglomeration of 1 ?200,000 people about the year 2000, the comprehension of the urban processes that make this transformation possible, it is the target to reach, the proper urban materiality, but also the performance of the inhabitants of the city, they will be able to be the regarding ones that allow to identify the driving elements of the transformations in the different moments of the XXth century. The investigation is realized from the proposal of a model of analysis, by means of which the temporary space of the XXth century splits into five periods differentiated by urban identifiable facts that could indicate the big thematic lines of urban transformation happened during the century, taking as a precedent the historical city that materializes in the foundation of 1576, coming until the proper XXth century with all his historicity, there raises the presence of the period of the first urban important transformation, which we call premodern, that would initiate the transition of the historical city to a city in expansion towards the half of the XXth century; there is identified also a period in which the search of the urban planning of this process of expansion would be the constant, this period would come up to the decade of 1980, which is when the city of León manages to have his first plan of urban development.

Las transformaciones urbanas en León del siglo XX son el tema de esta investigación, la ciudad que se estudia, que en el principio de siglo tendría una forma urbana pre moderna, hacia el final del mismo siglo se habría transformado en una forma urbana con características metropolitanas pasando de ser el espacio materializado de una sociedad de cien mil habitantes, a una aglomeración de 1 ?200,000 2 habitantes hacia el año 2000, la comprensión de los procesos urbanos que posibilitan esta transformación, es el objetivo a alcanzar, la propia materialidad urbana, pero también la actuación de los habitantes de la ciudad, podrán ser los referentes que permitan identificar los elementos impulsores de las transformaciones en los diferentes momentos del siglo XX. La investigación se realiza a partir de la propuesta de un modelo de análisis, por medio del cual el espacio temporal del siglo XX se divide en cinco períodos diferenciados por hechos urbanos identificables que puedan indicar las grandes líneas temáticas de transformación urbana ocurridas durante el siglo, teniendo como antecedente la ciudad histórica que se materializa en la fundación de 1576, llegando hasta el propio siglo XX con toda su historicidad, se plantea la presencia del período de la primera transformación urbana importante, que llamamos pre moderna, que iniciaría la transición de la ciudad histórica a una ciudad en expansión hacia la mitad del siglo XX; se identifica también un período en el que la búsqueda del ordenamiento urbano de este proceso de expansión sería la constante, este período llegaría hasta la década de 1980, que es cuando la ciudad de León consigue tener su primer plan de desarrollo urbano.
Facultad de Arquitectura. Programa Interinstitucional de Doctorado en Arquitectura
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2568; info:eu-repo/classification/cti/4; FA-D-2007-0004; Transformación urbana; Urbanismo; Arquitectura